2015
DOI: 10.18632/oncotarget.5028
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 is remarkably over-expressed in EBV-associated pulmonary lymphoepithelioma-like carcinoma and related to poor disease-free survival

Abstract: BackgroudProgrammed cell death-ligand 1 (PD-L1) and driver mutations are commonly seen in non-small-cell lung cancer (NSCLC). However, the prevelance of PD-L1 over-expression and its prognostic value in Epstein–Barr virus (EBV) associated pulmonary lymphoepithelioma-like carcinoma (LELC) remains poorly understood.MethodsA total of 214 NSCLC patients and 113 surgically treated pulmonary LELC patients were included. Paraffin-embedded tumor sections were stained with PD-L1 antibody. Correlations between PD-L1 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
69
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(74 citation statements)
references
References 35 publications
3
69
2
Order By: Relevance
“…In a report by Jiang et al, the PD-L1 (+) in TCs group was associated with longer DFS, which was consistent with our result (P=0.037) (5). In contrast, no prognostic value of this biomarker for LELC of lung was found in Chang and colleagues' retrospective analysis, and Fang et al had observed that high PD-L1 expression in TCs (H score ≥30) was correlated with poor DFS in resectable LELC of lung (4,6). Although there is no agreement on the prognostic significance of PD-L1, these published reports had confirmed that patients with primary pulmonary LELC are a special community with a higher incidence of PD-L1 (+) in TCs and that they might be candidates for immune therapy with PD-L1/PD-1 monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In a report by Jiang et al, the PD-L1 (+) in TCs group was associated with longer DFS, which was consistent with our result (P=0.037) (5). In contrast, no prognostic value of this biomarker for LELC of lung was found in Chang and colleagues' retrospective analysis, and Fang et al had observed that high PD-L1 expression in TCs (H score ≥30) was correlated with poor DFS in resectable LELC of lung (4,6). Although there is no agreement on the prognostic significance of PD-L1, these published reports had confirmed that patients with primary pulmonary LELC are a special community with a higher incidence of PD-L1 (+) in TCs and that they might be candidates for immune therapy with PD-L1/PD-1 monoclonal antibodies.…”
Section: Discussionmentioning
confidence: 94%
“…In limited literature reports, patients with primary pulmonary LELC survive longer than patients with other lung cancer subtypes (1)(2)(3). However, almost thirty-one percent of early stage patients experienced recurrence within five years after multimodality treatment, and nearly thirty-two percent of all patients with lung LELC presented with advanced disease at initial visits (1,(3)(4)(5). Thus, discovery of new therapeutic targets is needed to improve survival and quality of life further for recurrent or metastatic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Using immunohistochemistry (IHC) assays, several Chinese teams have reported prevalences of tumor cell PD-L1 cytoplasmic and/or membrane staining ranging from 39.9% to 65.9% on Chinese NSCLC patient samples [2631]. In our study, only PD-L1 membrane staining was used to define PD-L1 positivity, generating a positive staining prevalence of 43.1%, which is largely consistent with the 39.9% reported by Yang's group [29].…”
Section: Discussionmentioning
confidence: 99%
“…More research is needed to determine the optimal assay and cutoff for determining PD-L1 positivity. Three retrospective series analyzed PD-L1 expression in a total of 258 cases of LELC of the lung (11)(12)(13). The threshold for a positive result was membranous expression in >5% tumor cells.…”
Section: Discussionmentioning
confidence: 99%